Triplet chemotherapy in combination with anti-EGFR agents for the treatment of metastatic colorectal cancer: Current evidence, advances, and future perspectives. (January 2022) - Folprecht, Gunnar; Martinelli, Erika; Mazard, Thibault; Modest, Dominik P.; Tsuji, Akihito; Esser, Regina; Cremolini, Chiara; Falcone, Alfredo
Graphical abstract: Highlights: FOLFOXIRI has shown improved efficacy compared with doublet chemotherapy. Anti-EGFR therapy + triplet chemotherapy is a feasible treatment option for mCRC. The optimal doses of irinotecan, oxaliplatin, and 5-FU are yet to be determined. Trials are investigating intensified chemotherapy + anti-EGFR agents in RAS -wt mCRC. Abstract: Doublet or triplet chemotherapy regimens in combination with anti–epidermal growth factor receptor (anti-EGFR) monoclonal antibodies (mAb), such as cetuximab or panitumumab, or the anti–vascular endothelial growth factor mAb bevacizumab, are the current recommended standard of care therapies for unresectable metastatic colorectal cancer (mCRC). While the recommended dosing schedule for the triplet chemotherapy regimen with 5-fluorouracil, oxaliplatin and irinotecan (FOLFOXIRI) in combination with bevacizumab is well established, the optimal dosing of FOLFOXIRI in combination with anti-EGFR agents is unknown. Several randomized, phase 3 clinical trials of patients with mCRC have demonstrated improved survival and response rates with FOLFOXIRI, alone or when combined with bevacizumab, compared with doublet chemotherapy regimens. Trials of anti-EGFR agents in combination with FOLFOXIRI have also shown promising results. In this review, we summarize the emerging evidence regarding the safety and efficacy of anti-EGFR agents in combination with triplet chemotherapy regimens and discuss the potential for this combination as a future treatment option for patients with RAS -wild-type mCRC.